Evaluación del aprovechamiento de agua de lluvia para uso doméstico en Moyobamba - San Martín - Fachín Armas, Ana Karina (2005)
The objective of this research work was to evaluate the use of rainwater as a resource for domestic use in Moyobamba, showing information about the use and consume of water, physical, chemical and microbiological analysis of the rainwater as well as the economical analysis (cost/benefit) of the rainwater micro collecting system in the urban and countryside which is the area of the research. In order to evaluate the advantages of using rain water for domestic purposes, there was an analysis of the current demand of water in the urban and countryside areas within the area of influence of the ordinary weather station in Moyobamba worked out through the Thinssen polygon method, which established that in any point of the river basin the amount of rainwater is the same as the one registered by the closest pluviometer; the demand analysis process is based on a probabilistic sample survey. Complementary data is taken from the conventional use of water in homes during 8 days, getting interesting output. The application of this rainwater micro intake system let us evaluate the quantity of water and its domestic use, we used the SCAPT method (roof rainwater micro collecting system), which was a proposal from the pan-American Center of Sanitary Engineering and Environmental Sciences (CEPIS) and the Technical Support Unit for Basic Sanitary of the Rural Area (UNATSABAR). In terns of the quality of rainwater collected, there were physical, chemical and microbiological analyses. The SCAPT evaluation is another important component of the research, it goes beyond the simple rewarding calculus, it is a contribution that will help us to make up our minds strategically on the optimization of the hydro resources use for human consuming. According to the data obtained in this research the proposal is more rewarding in the countryside and it contributes meaningfully to improve its life quality, enlarging and guarantying the availability of water in their homes with an acceptable quality for human consuming.